2016
DOI: 10.1007/s12110-016-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Psychological Mechanisms in the Anthropology of Altruism

Abstract: Anthropologists have long been interested in the reasons humans choose to help some individuals and not others. Early research considered psychological mediators, such as feelings of cohesion or closeness, but more recent work, largely in the tradition of human behavioral ecology, shifted attention away from psychological measures to clearer observables, such as past behavior, genetic relatedness, affinal ties, and geographic proximity. In this paper, we assess the value of reintegrating psychological measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…In contrast, when asked about people outside the community who they did not know, respondents nearly always placed them in the farthest bin. The measures of closeness also showed strong independent associations with helping in the previous year (61).…”
Section: Adapting a Common Protocol: Social Discountingmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, when asked about people outside the community who they did not know, respondents nearly always placed them in the farthest bin. The measures of closeness also showed strong independent associations with helping in the previous year (61).…”
Section: Adapting a Common Protocol: Social Discountingmentioning
confidence: 82%
“…In interviews, respondents mentioned that ghonishto friends and relatives feel comfortable around each other; enjoy visiting each other; help each other with chores, loans, and advice; and trust each other enough to talk freely, or "open their minds," to each other about important, sensitive, and secretive matters. The factors described as making people feel less close included envy; regular failures to help when needed; conflicts over lending and borrowing; fights between one's children; and disputes over farmland, livestock, and situations where another's cattle ate one's crops (61). Another potential source of conflict was worry that an envious friend had used supernatural tools (amulets and spells) to cause injury or illness.…”
Section: Adapting a Common Protocol: Social Discountingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the U.S., we recruited 40 participants via emails sent to a list of 6000 undergraduates, curated by the Center for Behavior, Institutions, and the Environment. In Bangladesh, we recruited one participant from each of 200 households across four villages in Northwestern Bangladesh (54). In Indonesia, we recruited 44 participants using opportunity sampling from a single rural settlement (nagari) in West Sumatra, near the city of Payakumbuh in the Lima Puluh Kota regency, limiting recruitment to 2 individuals from the same household.…”
Section: Methodsmentioning
confidence: 99%
“…At present, there have been many researches on the analysis of psychological factors in linguistics, and especially for English and the minority languages (Gutenstein, 2014), some researchers have been conducted on students' learning thinking and foreign language expression. From this, it's concluded that psychological factors play a major role in language learning and language expression (Sopha & Klöckner, 2011); some college students are not good at organizing language or understanding the structural relationship of language (Feinstein, 2012), which is closely related to the psychological obstacles such as nervousness, anxiety and timidity (Hackman, Munira, Jasmin et al, 2016); the psychological mechanism in the language expression process for college students can significantly influence the process of psychoanalysis, and further their language expression ability (Antiel, Curlin, James et al, 2013). Therefore, the study on the college students' psychological factors and psychological mechanisms in the process of language expression can effectively improve their language ability of expression.…”
Section: Introductionmentioning
confidence: 99%